Diffuse reticulate purpura in two adolescents with anorexia nervosa and severe malnutrition. Issue 3 (15th April 2021) - Mateos‐Mayo, Ana; Anderson‐Vildósola, James; Morón‐Nozaleda, María Goretti; Camarneiro, Ricardo; Escribano, Eva; Colmenero, Isabel; Torrelo, Antonio; Hernández‐Martín, Ángela
Abstract: Anorexia nervosa is an eating disorder frequently associated with cutaneous manifestations. A rare type of purpura, known as diffuse reticulate purpura, has been described in patients with anorexia nervosa and severe malnutrition. Typical characteristics of this condition include a purpuric reticulate rash predominantly affecting the trunk that rapidly resolves with adequate feeding. We report two male adolescent patients with anorexia nervosa and severe malnutrition who developed diffuse reticulate purpura.